(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2022)
The period was colored by films of different genres but there are still many weaknesses that hinder the progress of national films. This research is aimed at describing the condition of Indonesian cinema in 1992-1998, presenting the development of Indonesian politics in 1998-2019, analyzing the political influence on Indonesian cinema in 1998-2019, and analyzing the development of Indonesian cinema in the face of the development of other media to watch films in 1998-2019. This research uses historical research methods that begin from the heuristic stage or source collection, criticism. source, interpretation of source data, and historical writing or historiography. This research uses historical research methods that begin from the heuristic stage or source collection, source criticism, interpretation of source data, and historical writing or historiography. The results of this study can be found that in 1998-2019 Indonesian cinema experienced ups and downs, it can be seen from the number of productions, audience numbers, and number of box office films. However, since the period 2016-2019 the development of national cinema has increased significantly. This can be seen from the increase in the number of screens and cinemas, the number of productions, the number of viewers, the number of box office films, and films that get appreciation abroad. 82.8%.